2019
DOI: 10.1111/aos.14148
|View full text |Cite
|
Sign up to set email alerts
|

Scleral and conjunctival features in patients with rhegmatogenous retinal detachment undergoing scleral buckling: an anterior segment optical coherence tomography and in vivo confocal microscopy study

Abstract: Purpose: To investigate the scleral and conjunctival features in patients with rhegmatogenous retinal detachment (RRD) undergoing scleral buckling (SB), using anterior segment optical coherence tomography (AS-OCT) and in vivo confocal microscopy (IVCM). Methods: Twenty RRD eyes were consecutively enrolled. AS-OCT was performed at RRD diagnosis (RRD-D) and day 1, week 1, month 1 and month 6 after SB to evaluate the sclera, in the affected and unaffected quadrants (AQ, UQ). IVCM was performed at RRD-D, and at mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Thus, we cannot be sure that scleral changes were clear signs of a uveoscleral outflow increase. However, given that such scleral features were previously proposed as AHUO biomarkers in a similar CB procedure (the UCP) and also in patients with rhegmatogenous retinal detachment [ 25 ], in which AHUO clearly increased, we think that our hypothesis is reasonable. Third, since AS-OCT cannot visualize structures located beyond the iris pigmented epithelium, we could not assess the effects of the procedure on the CB.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, we cannot be sure that scleral changes were clear signs of a uveoscleral outflow increase. However, given that such scleral features were previously proposed as AHUO biomarkers in a similar CB procedure (the UCP) and also in patients with rhegmatogenous retinal detachment [ 25 ], in which AHUO clearly increased, we think that our hypothesis is reasonable. Third, since AS-OCT cannot visualize structures located beyond the iris pigmented epithelium, we could not assess the effects of the procedure on the CB.…”
Section: Discussionmentioning
confidence: 65%
“…The MISHA and SR were calculated with Image J, which is an open-source software for processing and analyzing scientific images (Image J software, version 1.52°, , accessed on 1 September 2023). As previously defined, intra-scleral hypo-reflective spaces are intra-stromal features in which the sclera presents well-defined areas with less intense reflectivity than the surrounding regions [ 16 , 25 ]. These hypo-reflective spaces should be intended as areas where the scleral stroma is loosely arranged and less compact and, therefore, with probably lower hydraulic resistivity.…”
Section: Methodsmentioning
confidence: 99%
“…OCTA debut has mainly increased the assess of the retinal vasculature, preceding important papers described various applications of OCTA technology for non-invasive imaging of the AS [2,17,[27][28][29][30]. Ang et al [27][28][29] reported corneal and limbal vasculature changes using AS-OCTA providing interesting insights on pathologic corneo-limbal features such as postherpetic scarring and limbal stem cell deficiency [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Rhegmatogenous retinal detachment (RRD) represents a common cause of visual impairment secondary to separation of neurosensory retina from the underlying retinal pigment epithelium (RPE) [1]. The RRD development typically involves the association between posterior vitreous detachment and one or more retinal breaks causing the fluid passage through the retinal breaks into subretinal space [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation